Effects of concave thoracoplasty on chest circumference and ventilatory function in adolescence with idiopathic scoliosis - Khaled Takey Ahmed; Abla Mohamed Hamed; Youssry El Hawary; Nesreen G. El-Nahas; Akram M. Helmy; Mohammed Hesham Aboelenien (Physiotherapy Quarterly)
Introduction Adolescent idiopathic scoliosis (AIS) can reduce rib cage volume, which mechanically overloads the respiratory musculature. A current study examines the influences of concave thoracoplasty on pulmonary function and chest circumference.